2021
DOI: 10.1186/s10195-021-00570-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of short-term outcomes of anterolateral supine approach and posterolateral approach for primary total hip arthroplasty: a retrospective study

Abstract: Background This study aims to evaluate postoperative pain and functional and clinical outcomes of anterolateral supine (ALS) and posterolateral (PL) approaches for primary total hip arthroplasty. Materials and methods We retrospectively examined the joints of 110 patients who underwent primary total hip arthroplasty (THA). The ALS group was compared with the PL group using the pain visual analog scale (VAS) and narcotic consumption as pain outcomes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 31 publications
1
13
0
Order By: Relevance
“…Yoshimura et al 19) reported that sarcopenia patients showed a lower discharge-tohome rate and lower ADL at discharge. In this study, results were similar to those described by Yoshimura et al Regarding the surgical approach, Ukai et al 20) reported a comparison of ALS and PL approaches, external rotation muscle strength of the hip joint was significantly weaker in the PL approach until half a year postoperatively. In addition, The ALS group started using a cane earlier and showed a shorter hospital stay.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Yoshimura et al 19) reported that sarcopenia patients showed a lower discharge-tohome rate and lower ADL at discharge. In this study, results were similar to those described by Yoshimura et al Regarding the surgical approach, Ukai et al 20) reported a comparison of ALS and PL approaches, external rotation muscle strength of the hip joint was significantly weaker in the PL approach until half a year postoperatively. In addition, The ALS group started using a cane earlier and showed a shorter hospital stay.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, The ALS group started using a cane earlier and showed a shorter hospital stay. In this study, both patients in the sarcopenia group were treated using the PL approach, and the surgical techniques might have been affected in a similar manner to those in the study by Ukai et al 20) .…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…4 studies focused more on component placement and outliers of cup alignment [8][9][10][11] , while the other 4 studies evaluated mostly intraoperative and postoperative outcomes. [12][13][14][15] The remaining study 16 was not included in the meta-analysis due to the absence of the researched parameters.…”
Section: Included Studiesmentioning
confidence: 99%
“…[ 10 ] The ALA was performed thought the gluteus medius, which was associated with increased hip load, decreased the dislocation rates,[ 11 ] and reduced length of stay (LOS). [ 12 , 13 ] Currently, the PLA remains the most commonly used in the United States, with an excellent exposure view by damaging joint capsule with shorter duration, lower intraoperative fracture, and higher risk of dislocation. [ 14 ] Overall, the efficacy and comparison between the approaches and the postoperative LLD and offset has not been sufficiently investigated with controversial findings.…”
Section: Introductionmentioning
confidence: 99%